Apoptose e proliferação celular na endometriose: estado da arte - Subtil,Simone (2016)
Endometriosis is a disease characterized by the ectopy of endometrial glands and stroma, which can significantly compromise the quality of life in childbearing-age women. Its etiology remains uncertain since retrograde menstruation does not completely explain the endometriosis implant fixation process. Apoptosis and cellular proliferation, fundamental processes to endometrial tissue homeostasis, present changes in the endometrium of women who suffer from this disease, which may help to explain its pathogenesis. Hormonal treatment usually controls symptoms associated with this disease. Its effects include the interference with the regulation of apoptosis and cellular proliferation. The objective of this review is to highlight the main subcellular environment changes in endometriosis, referring to the factors that regulate apoptosis and cellular proliferation, and how all those factors evolve with the hormonal treatment.